Early Outcome of Bifurcational Coronary Artery Stenting - Bedair, Ahmed Y.; Farhan, Hasan Ali; Jabir, Usama (AL-Kindy College Medical Journal, 2011)
BACKGROUND : Bifurcational coronary lesions are frequent and amounts to almost one fifth of routine practice concerning up to 15 – 20 % of cases . Revascularization by percutaneous coronary intervention ( PCI ), of bifurcational lesion has become easier by stenting yet it remains a frequent challenge. OBJECTIVE : To evaluate the success and hospital complications of two most frequent technique of stent deployment in bifurcational PCI. METHODS : We prospectively analysed the data of 140 consecutive patients with bifurcational PCI at Ibn_Al-Bitar Hospital for cardiac surgery for the period from July 2008 to July 2009 . Depending on whether the side branch was stented or not, the patient has fallen into two groups : - Group A; stenting of the main vessel and angioplasty of the branch. Group B; stenting of both main vessel and its branch . The early outcome of the bifurcational PCI and all complications during hospitalization that include; death, acute Myocardial infarction , emergency percutaneous treatment and coronary artery bypass graft (CABG) were evaluated in the studied groups. RESULTS : The studied sample consisted of 140 patients,107(76.3%)were male and 33(23.7%) were female. Group A consisted of 90 patients (64.3%) while group B consisted of 50 patients(35.7%).Acute procedural success was (94.2%) in group A and (80%) in group B while hospital major adverse cardiac event(MACE) were noted in 3.8% of group A and 20% of group B,(PV=0.04) CONCLUSION: In bifurcational PCI stenting of the side branch has made no extra advantage in term of procedural success and early outcome.